The effect of time management strategy on improving some football skills (Journal of the College of Basic Education, 2022)
Many countries have taken into account education systems in a focused manner, because of their importance in building their societies, their development and progress for the better. What we notice is that there is strong competition among developed countries that are looking for leadership in various fields, and this indicates that these countries have given attention to the educational process The educational and educational methods followed the correct, developed and modern methods in order to obtain that lead. The student, the teacher, the curriculum and the place in which the teaching process takes place are one undivided unit. If one of these axes suffers from weakness, the rest of the axes weaken